Mesenchymal stem cell interaction with a non-woven hyaluronan-based scaffold suitable for tissue repair - Pasquinelli, G (Blackwell Science Inc, 2008)
The fabrication of biodegradable 3-D scaffolds enriched with multipotent stem cells seems to be a promising strategy for the repair of irreversibly injured tissues. The fine mechanisms of the interaction of rat mesenchymal stem cells (rMSCs) with a hyaluronan-based scaffold, i.e. HYAFF®11, were investigated to evaluate the potential clinical application of this kind of engineered construct. rMSCs were seeded (2 × 10(6) cells cm(−2)) on the scaffold, cultured up to 21 days and analysed using appropriate techniques. Light (LM), scanning (SEM) and transmission (TEM) electron microscopy of untreated scaffold samples showed that scaffolds have a highly porous structure and are composed of 15-µm-thick microfibres having a rough surface. As detected by trypan blue stain, cell adhesion was high at day 1. rMSCs were viable up to 14 days as shown by CFDA assay and proliferated steadily on the scaffold as revealed by MTT assay. LM showed rMSCs in the innermost portions of the scaffold at day 3. SEM revealed a subconfluent cell monolayer covering 40 ± 10% of the scaffold surface at day 21. TEM of early culture showed rMSCs wrapping individual fibres with regularly spaced focal contacts, whereas confocal microscopy showed polarized expression of CD44 hyaluronan receptor; TEM of 14-day cultures evidenced fibronexus formation. Immunohistochemistry of 21-day cultures showed that fibronectin was the main matrix protein secreted in the extracellular space; decorin and versican were seen in the cell cytoplasm only and type IV collagen was minimally expressed. The expression of CD90, a marker of mesenchymal stemness, was found unaffected at the end of cell culture. Our results show that HYAFF®11 scaffolds support the adhesion, migration and proliferation of rMSCs, as well as the synthesis and delivery of extracellular matrix components under static culture conditions without any chemical induction. The high retention rate and viability of the seeded cells as well as their fine modality of interaction with the substrate suggest that such scaffolds could be potentially useful when wide tissue defects are to be repaired as in the case of cartilage repair, wound healing and large vessel replacement.